The Effect of Nasal Irrigation on The Severity of Nasal Obstruction among Toll Gate Officers : A Randomized Controlled Trial - Faradis Karmilah MH; Anna Mailasari Kusuma Dewi (Faculty of Medicine, Diponegoro University, 2025)
Background: Traffic-related air pollution can trigger inflammation of the nasal tissues, potentially leading to nasal obstruction. Toll gate officers are at risk of exposure to this pollution. Nasal irrigation with isotonic saline solution can lessen the symptoms of nasal obstruction.Objective: To evaluate the effect of nasal irrigation on the severity of nasal obstruction on toll gate officers.Methods: This true experimental study employed a randomized controlled trial (RCT) with a pre-and posttest design. A total of 42 toll gate officers from Jasamarga Company, Semarang, participated in the study. Two groups were formed from the participants: one received the treatment, the other served as a control. Participants in the treatment group received nasal irrigation with isotonic saline solution once daily for 14 days. Nasal obstruction was evaluated using the NOSE Scale and PNIF. Statistical analyses were accomplished using the T-test, Wilcoxon test, and Mann-Whitney U test.Results: A clear difference was detected in the degree of nasal obstruction, both as measured by NOSE Scale (p=0,018) or PNIF (p=0,014 ; 95% CI, 4.19 to 34.86). The degree of nasal obstruction using NOSE Scale within the treatment group decreased significantly (p = 0.035) in comparison to control group (p = 0.341). The degree of nasal obstruction using PNIF measurement in the treatment group decreased significantly (p = 0.002 ; 95% CI, -34.16 to -9.17) compared with the control group (p = 0.651 ; 95% CI, -5.89 to 9.23).Conclusion: Nasal irrigation with isotonic saline solution significantly reduces the severity of nasal obstruction.